A review of supply chain integration extents, contingencies and performance : A post Covid-19 review. (2021) - Hassan, Nadir Munir; Abbasi, Muhammad Nauman
Abstract: This research intends to synthesize and analyze the existing research published with respect to "extent of supply chain integration" and impact of Multiple extents of supply chain integration on supply chain performance. Three fundamental questions, including; How the extent of supply chain integration has been defined and measured in the exiting SC literature? What are the bases of differences/inconsistencies in defining various extents of integration, and What is the impact of certain contingencies (i.e. moderators & situational factors) on a relationship between, supply chain integration (extents), and supply chain performance?. In desire of sketching the available extents of supply chain integration, and their impact on chains performance, an organized technique is made use of, to observe 293 (Ultimately trimmed to 113) research studies, within the time frame of Jan 1 st, 2015 till April 2020, gathered through multiple platforms, including, Emerald, Taylor & Francis, Wiley & Science Direct. Results of the study, generate the notable list of dimensions, performance outcomes, contingent variables, theoretical lenses and list of Industries which have been considered for studies in the field of SCI within the considered time frame.